External mechanical work versus oxidative energy consumption ratio during a basketball field test - Crisafulli, A.; Melis, F.; Tocco, F.; Laconi, P.; Lai, C.; Concu, A. (The Journal of Sports Medicine and Physical Fitness, 2002)
BACKGROUND: A field test consisting of 5 continuous runs at the maximum speed possible, playing the ball, starting from the centre line to the basket with a final shot, was studied in order to obtain an index of mechanical work efficiency in basketball players (micro-index=Jmec/Joxy) and evaluate the correlation between micro-index and velocity, acceleration, mechanical power and lactacid anaerobic capacity, respectively. METHODS: Eight male basketball players were studied; Jmec was the external mechanical work output obtained by means of a video image analysis software which gave the potential and the kinetic translational energies of athletes running and jumping and their velocity, acceleration and mechanical power. By means of a telemetric device (Kosmed K4), for measuring O2 consumption ( VO2), we obtained oxidative work (Joxy). By using this device we also assessed the excess of CO2, which was considered an index of lactacid anaerobic capacity. RESULTS: Non-parametric Spearman statistics revealed a significant correlation between &mgr;index and mean velocity (p<0.01, r=0.90), acceleration (p<0.05, r=0.78), mechanical power (p<0.05 r=0.76) and CO2 excess (p<0.01, r=0.95). Consequently athletes who had the best index of mechanical efficiency also had the best biomechanical quality and the greatest lactacid anaerobic capacity. CONCLUSIONS: This study strongly supports the hypothesis that in basketball anaerobic capacity is important in achieving high values of speed, acceleration, mechanical power and endurance velocity.